How to Use the New Florida Citrus Rootstock Selection Guide - Ferrarezi, Rhuanito Soranz; Castle, William S.; Bowman, Kim D.; Grosser, Jude W.; Futch, Stephen H.; Rogers, Steve; Gonzalez, Andres (EDIS, 2020)
First published in 1989 as Rootstocks for Florida Citrus, the work of Dr. William Castle and his colleagues remains relevant 30 years later. The purpose of the Florida Citrus Rootstock Selection Guide (FLCRSG) is to provide timely and useful citrus rootstock information to help Florida citrus growers make well-grounded, practical decisions. New problems with abiotic factors, pests, and diseases make the FLCRSG a standard document for the Florida citrus industry. Initially published as a book, it was integrated into an informative wheel and is now a web-based expert system with an interactive table with 21 characteristics of 48 rootstocks. Much has changed within the Florida citrus industry since the discovery and spread of the vector-transmitted disease huanglongbing (HLB). Rootstocks were not initially part of the discussion related to managing HLB, but that has changed, particularly given the accumulating evidence that trees on various rootstocks may differ in the incidence or tolerance of the disease. The authors have prepared this timely and necessary update of the former editions and have expanded the list of rootstocks. We revised the information on the UFR series and added three new U.S. rootstocks (US SuperSours) that have not yet undergone the usual extensive field evaluation in Florida. These new rootstocks offer improvements regarding HLB tolerance and several other meaningful traits, such as tree size, high yield, and juice quality that appear essential to the future of our citrus industry.